A Study on the Use of Blockchain Technology to Prevent and Detect Corruption in Thailand’s Government Procurement Process - Phimolsathien, Thepparat (My University, 2026)
This study aims to propose several recommendations for adopting blockchain to government procurement and for solving corruption. The results of the study can be summarized as: readiness of blockchain technology can prevent corruption and the level of readiness of blockchain adoption for government procurement and for solving corruption is low. The study proposes developing a blockchain system and a smart contract system in the selection of committees to enhance transparency via online grading both in the selection procedure and procurement projects, to undergo online e-government procurement training, and to develop an online grading system for the committees.
Keywords: Blockchain Technology; Government Procurement